A critical review of the world catalogs of Empidoidea (Insecta: Diptera) by Yang et al. (2006, 2007) - Sinclair, Bradley J.; Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2008)
Many in the worldwide Diptera taxonomic community were surprised to see the recent publication of the “World Catalog of Dolichopodidae (Insecta: Diptera)” by Yang, Zhu, Wang & Zhang (2006) and the “World Catalog of Empididae (Insecta: Diptera)” by Yang, Zhang, Yao & Zhang (2007). The rapid completion of both catalogs that together report to cover all of the world’s empidoid diversity, the apparent lack of peer review, and the higher classification schemes adopted in these works, appear to have created considerable scepticism and discussion on the extent of their usefulness by empidoid workers. As O’Hara (2008) recently stated “modern technological advances make it possible for just about anyone to compile names from the Zoological Record, to scan catalogues, and to gather information from secondary sources to produce an unimpressive world catalogue in record time”. In order to accurately assess the value of these two catalogs, especially for current and future users, we provide a critical review that touches on all aspects of these contributions. It is not our intention to give a page by page critique, but instead to provide a summary of the types of errors and omissions (illustrated with examples) we have encountered and to point out the limitations of these catalogs while also indicating which parts are useful in a general sense.